Blood transfusion knowledge and practice among nurses in Turkey: A scenario sample - Asiye Durmaz Akyol; Hülya Kankaya; Filiz Özel; Gülbin Konakçı (Ovid Technologies (Wolters Kluwer Health), 2023)
BACKGROUND: In the maintenance of this important application, it is very important to ensure safety and to prevent complications. Therefore, it must be careful in the transfusion of blood and blood component. AIM: The aim of the study was to define nurses’ blood transfusion-related knowledge levels and applications. STUDY SETTINGS AND DESIGN: The study sample consisted of nurses who worked in a medical faculty hospital, two education and research hospitals and two state hospitals in Turkey. The study was performed with 116 nurses. MATERIALS AND METHODS: “Nurse Information Form”, “The Blood Transfusion Knowledge Questionnaire” and “The scenario form and a video taken on the errors and drawbacks related to blood transfusion” were used as data collection instruments. STATISTICAL ANALYSIS USED: The statistical analysis was performed using SPSS for Windows version 17.0. The sociodemographic data obtained from the study were assessed by numbers frequency and percentage distribution. The blood transfusion knowledge scores of the independent variables and, the relationship between knowledge scores and units were analysis by chi-square, Mann Whitney-U and, Kruskal–Wallis tests. RESULTS: The nurses’ mean scores for the blood transfusion knowledge level were 61.81 ± 10.18 (ranging between 0 and 79) for the overall scale. There was a significant relationship between the clinics and questions on pre-transfusion patient preparation knowledge and their mean total knowledge score. The nurses’ mean scores for the blood transfusion-related scenario knowledge levels were 36.42 ±15.42 for the overall scenario scores. CONCLUSIONS: Based on this, the nurses’ knowledge levels about blood transfusion are partly adequate in terms of their mean knowledge scores, and insufficient in terms of their mean scenario knowledge scores.
Keywords: knowledge; Diseases of the blood and blood-forming organs; Original Article; blood transfusion; RC633-647.5; nurses; scenario